2019
DOI: 10.1021/acs.orglett.8b03501
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Cellular Uptake of Oligonucleotides Bearing Glutathione-Labile Protecting Groups

Abstract: Glutathione-labile protecting groups for phosphodiester moieties in oligonucleotides were designed, synthesized, and incorporated into oligonucleotides. The protecting groups on the phosphodiester moieties were cleaved in a buffer containing 10 mM glutathione, which was used as a model of intracellular fluid. Cellular uptake of oligonucleotides bearing glutathione-labile protecting groups was strongly affected by the location and number of the protecting groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
7
0
2
Order By: Relevance
“… 102 While relaxed single AOCs 24 showed poor activity, 6 Abe and co-workers introduced phosphoramidite 32 for use in automated DNA and RNA synthesis. 103 105 Dependent on their positioning, the presence of 5–10 AOCs 32 resulted in efficient cytosolic oligonucleotide delivery. Peptide-based oligomers of COCs, together with the introduction of cell-penetrating streptavidin, also showed that multivalency of COCs strongly increases uptake.…”
Section: Privileged Scaffoldsmentioning
confidence: 99%
“… 102 While relaxed single AOCs 24 showed poor activity, 6 Abe and co-workers introduced phosphoramidite 32 for use in automated DNA and RNA synthesis. 103 105 Dependent on their positioning, the presence of 5–10 AOCs 32 resulted in efficient cytosolic oligonucleotide delivery. Peptide-based oligomers of COCs, together with the introduction of cell-penetrating streptavidin, also showed that multivalency of COCs strongly increases uptake.…”
Section: Privileged Scaffoldsmentioning
confidence: 99%
“…After cellular uptake, the protecting groups are deprotected by esterase or GSH to release active RNA species. However, special synthetic procedures are needed for the preparation of these RNAs. In our laboratory, bioreduction labile protecting groups have been used for the development of reduction-activated DNA type oligonucleotides that can be activated by the hypoxic conditions found in advanced solid tumors. , These oligonucleotides were also amenable to solid-phase DNA synthesis and purification. To expand our study into reduction-activated RNA type molecules, development of bioreduction labile 2′-hydroxyl protecting groups is critical.…”
mentioning
confidence: 99%
“…Bioreduction of this type has been seen before in an E. coli NADH-dependent nitroreductase. 44 To assess the product of the reactions we followed the protocol published for a similar reductase. 45 Large-scale reactions were performed using CNR to reduce three compounds (26h, 27h, and 28h), representative of each family synthesized with the same 4-bromophenyl group.…”
mentioning
confidence: 99%